Preserving Indigenous Knowledge: A Case Study of the Audiovisual Archives of the International Centre for African Music and Dance (ICAMD) - Adjei, Emmanuel (Ghana Library Journal, 2005)
Archives are part of our cultural heritage. Acquiring, processing and providing access to recorded in formation are some the reasons why archival institutions exist. The functions of the ICAMO archives are no different. It is an audiovisual archive with collections of African music and dance dating back to the 1950s. That this heritageis worth preserving is the theme of this study. The state-of-the art in the preservation of audio and video recordings are investigated, problems which come to light discussed and feasible solutions prescribed. Face-to-face interview and observation were the instruments considered appropriate for the study. The study revealed that while some positive arrangements are in place, current preservation effort by the ICAMO lacks focus and coordinated planning. A lot more needs to be done by way of providing the necessary resources and the appropriate facilities supported by comprehensive institutional policies on acquisitions and access.